The effect of L-carnitine on insulin resistance in hemodialysed patients with chronic renal failure - Günal, AI; Celiker, H; Dönder, E; Günal, SY (Wichtig Editore, 1999)
We investigated the effect of L-carnitine in seven patients, four female and three male (mean age 44.4 +/- 6.0 years) with chronic renal failure. Six patients, four female and two male (mean age 49.3 +/- 2.2 years) with chronic renal failure were given a placebo (0.9% sodium chloride) as control, After the basal data were obtained, patients received a single intravenous dose of L-carnitine (1 g) or placebo and two hours later insulin sensitivity was studied by the intravenous insulin tolerance test. No change was observed in biochemical data and K-itt values in the placebo group, K-itt increased significantly with carnitine (from 2.99 +/- 0.3 to 3.54 +/- 0.2%/min, p < 0.03) compared to the control group (p < 0.02). This result suggests that L-carnitine may improve the insulin resistance common among uremic patients.
Keywords: chronic renal failure; insulin resistance; L-carnitine